2021
DOI: 10.3390/cells10030653
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 Expression Is Associated with Epithelial–Mesenchymal Transition (EMT), Cell Proliferation, Prognosis, and Drug Response in Pancreatic Cancer

Abstract: Annexin A1 (ANXA1) is a calcium-dependent phospholipid-binding protein overexpressed in pancreatic cancer (PC). ANXA1 expression has been shown to take part in a wide variety of cancer biology, including carcinogenesis, cell proliferation, invasion, apoptosis, and metastasis, in addition to the initially identified anti-inflammatory effect in experimental settings. We hypothesized that ANXA1 expression is associated with cell proliferation and survival in PC patients. To test this hypothesis, we analyzed 239 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…For example, ANXA1 has tumor suppressor roles in prostate, oral squamous cell [29] and head and neck cancer [30]. On the contrary, ANXA1 has tumor promoter roles in pancreatic cancer [31], breast cancer [32], liver cancer [33], lung cancer [34], thyroid cancer [24] and esophageal cancer [35]. Our study results add another piece of evidence that ANXA1 plays various roles in different cancer types and its complex regulation mechanisms.…”
Section: Discussionmentioning
confidence: 51%
“…For example, ANXA1 has tumor suppressor roles in prostate, oral squamous cell [29] and head and neck cancer [30]. On the contrary, ANXA1 has tumor promoter roles in pancreatic cancer [31], breast cancer [32], liver cancer [33], lung cancer [34], thyroid cancer [24] and esophageal cancer [35]. Our study results add another piece of evidence that ANXA1 plays various roles in different cancer types and its complex regulation mechanisms.…”
Section: Discussionmentioning
confidence: 51%
“…The activity of UPR was quantified as the degree of enrichment of the "HALLMARK_UNFOLDED_PROTEIN_ RESPONSE" gene set (Table S1 lists all the genes included in this gene set) defined and generated as one of the Hallmark gene set collections of the Molecular Signatures Database (MSigDB) [20] using the gene set variation analysis (GSVA) algorithm [21] in the Bioconductor package (version 3.10). We have previously reported the clinical relevance of multiple signaling pathways and responses using a similar approach [12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a deficiency in FPR2 has been related to a sustained polarization toward an M1 phenotype in hepatocellular carcinoma [ 216 ]. Moreover, the role of AnxA1 in inducing TH2 cells infiltration in pancreatic cancer [ 235 ] and in inducing the differentiation and expansion of Tregs in the TME of triple-negative breast cancer models has also been described [ 100 ]. Bai and collaborators showed that the proliferation of effector T cells, when treated with Ac2-26, was lower and that the function of Tregs was impaired when these cells were treated with the FPR inhibitor Boc1.…”
Section: Structure and Functions Of Annexin A1mentioning
confidence: 99%